Economic impact of hiking tourism on the Selo route in Mount Merbabu National Park: An estimation of the multiplier effect analysis - Hasan, Muhammad Aqil (Journal of Socio-Cultural Sustainability and Resilience, 2024)
Background: Mount Merbabu is one of the famous natural tourist attractions in Central Java, and it is known for its stunning natural panorama. Climbers who explore Mount Merbabu can enjoy spectacular views of the sunrise, the sea of ​​clouds, and the rows of mountain peaks around it. Tourism activities along the Selo Hiking Trail impact the local community's social and economic aspects, both directly and indirectly. This study aims to identify the social impacts and estimate the economic impact of tourism on the community along the Selo Hiking Trail. Methods: This study uses the Multiplier Effect analysis method to evaluate the economic impact of tourism activities. This method involves measuring several economic indicators, including the Keynesian Income Multiplier, Type I Ratio Income Multiplier, and Type II Ratio Income Multiplier, to determine the effect of tourism activities on the local economy. Findings: The study results indicate that tourism activities along the Selo Hiking Trail have a significant economic impact. The Keynesian Income Multiplier value reaches 0.6, the Type I Ratio Income Multiplier is 3.3, and the Type II Ratio Income Multiplier is 3.5. This indicates that tourism activities positively affect the income of the surrounding community and encourage local economic growth. Conclusion: From the analysis results, it can be concluded that tourism on the Selo Hiking Trail has a positive economic impact through the multiplier effect. However, further research is needed to focus on culture-based tourism or Community-Based Tourism in the surrounding villages to increase the economic benefits for the surrounding community. Novelty /Originality of this article: This study introduces the Multiplier Effect analysis approach in evaluating the economic impact of tourism on Mount Merbabu, providing new insights into the economic contribution of tourism to local communities. These findings also highlight the importance of developing culture-based tourism to expand local communities' economic and social benefits.